(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Two new species of the genus Ancylis Hubner, [1825], (Lepidoptera Tortricidae) are described from Progranitchnyj region and Ussuriysk region of Russian Far East, Ancylis barabashi sp.n. and Ancylis ussuricana sp.n. Ancylis barabashi Trematerra & Li sp.n. is close to Ancylis sculpta Meyrick, 1912, and Ancylis ussuricana Trematerra & Li sp.n. is similar to Ancylis badiana (Denis & Schiffermuller, 1775). The new species can be easily separated by a few morphological characters of the male genitalia.